Bank diversification and performance in an emerging market - Duho, K.C.T.; Onumah, J.M.; Owodo, R.A. (International Journal of Managerial Finance, 2019)
Purpose – The purpose of this paper is to investigate the impact of diversification on profitability, profit efficiency and financial stability of Ghanaian banks. Design/methodology/approach – The authors employed a panel regression technique on a data set of 32 banks from 2000 to 2015. The data envelopment analysis is used to compute profit efficiency scores with credit risk accounted for. Findings – The results suggest that income diversification decreases profit, profit efficiency and financial stability. The impact on profit and stability is U-shaped. The impact of asset diversification was found to be insignificant. High competition reduces both profitability and profit efficiency which is inconsistent with the quiet-life hypothesis of Hicks (1935), but financial stability increases with competition. High investment in tangible assets is associated with poor performance. Non-banking financial institutions that later became universal banks are not financially stable. Competition, size, age, government ownership and leverage which are controlled for and a sensitivity analysis conducted also provided relevant insights. Practical implications – The results are relevant in understanding the events in the Ghanaian banking industry in 2017–2018. Income diversification strategy is essential in determining the performance of banks. Management has to figure out the extent and scope of their diversification to benefit from the strategy. Originality/value – The authors examined diversification from the view-point of both the income statement and statement of financial position while most prior studies focused on only one aspect. The study is one of the few studies that employed the risk-adjusted profit efficiency measure in Sub-Saharan Africa.
Research Article
Keywords: Ghana; Data envelopment analysis; Profit efficiency; Credit risk; Financial stability; Diversification strategy